BENTHIC SEDIMENT INFLUENCE ON DISSOLVED PHOSPHORUS CONCENTRATIONS IN A HEADWATER STREAM - Lottig N.R.; Stanley E.H. (My University, 2007)
Phosphate interacts with inorganic sediment particles through sorption reactions in streams. Collectively, this phosphorus (P) buffering mechanism can be an important determinant of soluble reactive P (SRP) concentrations. If sorption reactions control SRP concentrations in a stream, then differences in sediment characteristics may cause spatial differences in SRP concentrations. This prediction was tested by examining sediment-buffering characteristics and spatial variation in SRP among reaches with distinct sediment composition (i.e., fine versus coarse particles) in two tributaries of Boulder Creek, a headwater stream in central Wisconsin. SRP concentrations were significantly lower and algal available P and P sorption capacity were significantly higher in the reach dominated by fine sediments. Although fine particles such as sand had the greatest P sorption capacity, no retention could be attributed to biotic processes, whereas over 50% of P retention in coarse particles such as gravel could be linked to biotic uptake. Equilibrium P concentration (EPC0) assays from different sediment fractions also indicate that biotic uptake is relatively unimportant in sand particles (EPClive 10 μg/L: EPCkilled 10 μg/L) but very important in gravel or larger particles (EPClive 10 μg/L: EPCkilled 80 μg/L). Thus, sediment influence on stream water P concentrations can shift predictably from abiotic sorption in reaches with fine particles to biotic retention in areas dominated by coarse sediments. Consequently, changes in sediment composition due to natural or anthropogenic disturbance have the potential to alter the type and strength of sediment-associated processes determining ambient stream P concentrations.
Keywords: PHOSPHORUS RETENTION; SEDIMENTS; EQUILIBRIUM PHOSPHORUS CONCENTRATION; EPC; EXTRACTABLE PHOSPHORUS; STREAMS